Nutritive Value or Bioutilization Technology of Alternative Forages for Ruminant Nutrition (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
To improve the efficiency of ruminant and livestock production, ruminant feeding should use local feed resources to develop alternative feeds or implement bio-utilization technologies to make use of byproducts, reduce feeding costs and alleviate the food competition between humans and animals. Feed constitutes a major input to the animal production system, and the nutritional value of alternative forages varies greatly depending on the source, variety, processing or storage method. Therefore, it is critical to understand feed quality and its impact on ruminant production, livestock product quality and the environment. Most importantly, we must describe the nutritional value of alternative feedstuffs with greater precision, allowing nutritionists to incorporate them into balanced diets with fewer errors, and improve feed quality through technological advancement. This Reprint aims to improve our understanding of the nutritive value of ruminant feeds, particularly roughage and silage. The main topics presented in this Reprint are: the nutritional value of ruminant feeds; non-conventional feed bioconversion for ruminants (including silage, yellow silage, ammonification, bacterial and enzymatic co-fermentation, etc.); and novel feedstuffs or unconventional feeds for ruminants, as well as their effects and mechanisms.